A Just Assemblage in Mental Health Services—the Necessity of and Possibilities for Service Diversity - Sundet, Rolf (Frontiers in Psychology, 2021)
Basic to the Norwegian welfare state is the principle of universality; every citizen has the right to equal health care and social services. Experiences from a family team in mental health care for children and adolescents exemplify challenges for mental health work in this welfare state. These experiences indicate an ongoing process of dismantling the welfare state, disguised as managerial changes and reorganizations. The argument is put forth that these changes and reorganizations that are claimed to benefit service users actually have negative consequences for many of them. These negative consequences are related to how psychological research on and knowledge of mental health and treatment are combined with organizational principles. The concept of an assemblage is introduced as a manner of describing the dominating relationships in health care between the medical model, the randomized controlled trial and new public management in order to provide responsible health care practices. Rooted in a supposition that how we look upon, describe and understand causation defines our views of science in general, how to produce knowledge, what kind of scientific knowledge is most productive, and how it should be implemented in practice, an alternative assemblage is suggested that better realizes the principle of universality. Here justice is about equal opportunities and equal rights to treatments and sets of practices that fit people as unique individuals. Such an assemblage would bring together diverse models of mental health care, a network of multiple research-based knowledges, and service organizations that include the differences and diversity of the population.